2014
DOI: 10.1016/j.bmcl.2014.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of arylpiperazines derivatives of 3,5-dioxo-(2 H ,4 H )-1,2,4-triazine as 5-HT 1A R ligands

Abstract: 5-HT1AR agonist or partial agonists are established drug candidates for psychiatric and neurological disorders. We have reported the synthesis and evaluation of a series of high affinity 5-HT1AR partial agonist PET imaging agents with greater selectivity over α-1AR. The characteristic of these molecules are 3,5-dioxo-(2H,4H)-1,2,4-triazine skeleton tethered to an arylpiperazine unit through an alkyl side chain. The most potent 5-HT1AR agonistic properties were found to be associated with the molecules bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In recent years much attention of chemists has arisen for the synthesis, chemistry and biological activity of 6-azauracil and their derivatives as a potential chemotherapeutic agent [1] such as, antibacterial and anti-tumor [2], anti-convulsant [3], inhibitors D-amino acid oxidase [4], imaging probe for 5-HT1A receptor agonist in nonhuman primates [5], [6], antimicrobial [7], and in mutations of the saccharomyces cerevisiae RPB1 gene conferring hypersensitivity to 6azauracil [8]. Most treatment of 6-azauracils with various electrophilic and/or nucleophilic reagents led to the formation of poly heterocyclic systems [9], [10], in addition produced oligonucleotides [11]- [18] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years much attention of chemists has arisen for the synthesis, chemistry and biological activity of 6-azauracil and their derivatives as a potential chemotherapeutic agent [1] such as, antibacterial and anti-tumor [2], anti-convulsant [3], inhibitors D-amino acid oxidase [4], imaging probe for 5-HT1A receptor agonist in nonhuman primates [5], [6], antimicrobial [7], and in mutations of the saccharomyces cerevisiae RPB1 gene conferring hypersensitivity to 6azauracil [8]. Most treatment of 6-azauracils with various electrophilic and/or nucleophilic reagents led to the formation of poly heterocyclic systems [9], [10], in addition produced oligonucleotides [11]- [18] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several members of this series such as 65 show nanomolar affinity for 5-HT 1A Rs, high selectivity over α 1 -AR, and potent agonist activity (Figure 26) [36]. The 1,2,3-benzotriazin-4-one terminal fragment characterizes some 5-HT 1A R antagonists prepared as potential antiproliferative agents in cancer cell lines [37].…”
Section: Modification Of the Terminal Fragmentmentioning
confidence: 99%
“…Additionally 5-HT 1A R agonist radiotracers may be useful to monitor desensitization and sensitization of receptors; to provide a better estimate of 5-HT 1A R in diseases; measure receptor occupancy of agonist therapeutic agents; and for the efficacy evaluation of SSRI treatment. The development of specific 5-HT 1A R agonist PET tracers has met with limited success despite three decades of effort . Most of the agonist radiotracers developed to date have the structural core of amino-tetralin, apomorphine, thiochromine, and arylpiperazine based ligands. We reported 3,5-dioxo-(2 H ,4 H )-1,2,4-triazine tethered arylpiperazines as promising agonist/partial agonist ligands with high affinity for 5-HT 1A R based on GTPγS stimulation studies in CHO cells stably expressing human 5-HT 1A R. Based on structure–affinity relationship (SAR) studies of 3,5-dioxo-(2 H ,4 H )-1,2,4-triazine, [ 11 C]­CUMI-101 was identified as a partial agonist radiotracer, and it has been tested in both nonhuman primates and human subjects with PET. Another study using membrane preparations from CHO cells also observed 5-HT 1A R agonist properties of CUMI-101 . However, the same report did not find stimulation of GTPγS binding by CUMI-101 in rat cortex and rat hippocampal membranes.…”
mentioning
confidence: 99%